Novel method for dynamic strength testing of laser brazed joints. Issue 1 (2020) - Overmeyer, Ludger; Wachsmuth, Steffen; Hermsdorf, Jörg; Reimann, Wilfried
Abstract: Laser brazed parts made of zinc-aluminum-magnesium (ZM) coated steel show a reduced mechanical performance compared to parts made of electrogalvanized (EG) steel. However, no outstanding difference of the strength was observed in quasi-static tensile shear tests. In order to characterize the dynamic strength, relevant for laser brazed hatchbacks in automotive industry, a novel testing method was developed. At the same load, EG samples resisted seven times more load cycles than those coated with ZM. This result illustrates the necessity of the novel testing method. Furthermore, the method enables a deeper understanding about the origin of the joints' deviant properties.